Keberhasilan Penginjilan Ingwer Ludwig Nommensen dalam Perspektif Teologi Penginjilan di Tanah Batak - Luciana Haryanto; Martha Mulyani Kurniawan (STIKAS Santo Yohanes Salib Kalimantan Barat, 2025)
The Great Commission (Matthew 28:19-20) says that the Lord Jesus commanded His disciples to preach the gospel and also applies to us as believers to carry out the Great Commission. In preaching the gospel, there are many risks and challenges that missionaries must face and most likely that is what makes most people afraid to preach the gospel, so they prefer to remain silent and keep the good news to themselves. We need to study mission figures who made their lives historic for others when they preached the gospel in a place. Through their experiences, they can give us motivation and enthusiasm to participate in preaching the gospel. The researcher will discuss an evangelistic figure named Nommensen. In his childhood, Nommensen once heard a story about a missionary told by his teacher named Callisen, since then he began to be interested in an event in the story, namely about the struggle to free backwardness, slavery of poor children. In general, Nommensen is known as a famous German evangelist in Indonesia. Because the fruit of his hard work was the establishment of the largest church in the Batak Toba ethnic group. Namely the Church called Huria Kristen Batak Protestan (HKBP). The success of evangelism carried out by Ludwig Ingwer Nommensen in Tanah Batak is one of the most prominent examples in the history of missions in Indonesia. This study explores Nommensen's evangelism strategy from the perspective of evangelism theology, by highlighting how his inculturative, educational, and social service approaches contributed to the acceptance of Christianity among the Batak people.